Analisis Tingkat Kepuasan Pengguna Apex Mobile Berdasarkan Rating Dan Ulasan Google Play Store Menggunakan Naïve Bayes - fauzi, abdul rahman; Saputra , Ananda Hadi; Abdillah, Muhammad Hasbi (Jurnal Riset Informatika dan Teknologi Informasi, 2023)
Apex Mobile Game is one of the most popular games on the Google Play Store. To improve game quality and provide users with a better gaming experience, analyzing online satisfaction based on Google Play Store ratings is very important for game developers. The purpose of this study is to analyze user reviews of the Apex Mobile game on the Google Play Store to determine the positive or negative sentiment of users. the opinion analysis method used is Naïve Bayes. This research begins with data collection, data preprocessing, feature extraction, training the Naive Bayes model and testing the model. The data used in the study were 10,000 reviews of the Apex Mobile game obtained through reviews from the Google Play store. The results showed that the majority of users were satisfied with Apex Mobile. This can be seen from 70% of users expressing positive feelings. However, this study also found other indications that there are some issues that need to be resolved, such as Bugs and Game Limitations. The results of this study can be used by game developers to improve quality and provide users with a better gaming experience.